2013
DOI: 10.1002/jbmr.1931
|View full text |Cite
|
Sign up to set email alerts
|

Multisite quantitative ultrasound for the prediction of fractures over 5 years of follow-up: The Canadian Multicentre Osteoporosis Study

Abstract: This study assessed the ability of multisite quantitative ultrasound (mQUS) to predict fracture over a 5-year follow-up. Participants were a subset of the Canadian Multicentre Osteoporosis Study. mQUS-assessed speed of sound (SOS in m/s) at three sites (distal radius, tibia, and phalanx) and extensive questionnaires were completed, after which participants were followed for 5 years and incident fractures recorded. Two survival analyses were completed for each site-a univariate analysis and an adjusted multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
(68 reference statements)
1
27
0
Order By: Relevance
“…Moreover, as ultrasound is composed of mechanical waves, it can be used to retrieve useful information on bone biomechanical properties and therefore provide information additional to that provided by bone mineral density (BMD) estimation alone (Ha€ ıat et al 2008a). QUS is now widely used in the clinic in the context of osteoporosis to estimate bone quality at such sites as the calcaneum (Chin and Ima-Nirwana 2013), phalanx (Olszynski et al 2013), tibia (Maatta et al 2014), femur (Barkmann et al 2008) and radius (Sasso et al 2009) using transverse (Mathieu et al 2013) and axial (Tatarinov et al 2014) transmission devices. Speed of sound (SOS) is a QUS parameter (Haiat et al 2005b) that has been found to be related to bone strength (Haiat et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as ultrasound is composed of mechanical waves, it can be used to retrieve useful information on bone biomechanical properties and therefore provide information additional to that provided by bone mineral density (BMD) estimation alone (Ha€ ıat et al 2008a). QUS is now widely used in the clinic in the context of osteoporosis to estimate bone quality at such sites as the calcaneum (Chin and Ima-Nirwana 2013), phalanx (Olszynski et al 2013), tibia (Maatta et al 2014), femur (Barkmann et al 2008) and radius (Sasso et al 2009) using transverse (Mathieu et al 2013) and axial (Tatarinov et al 2014) transmission devices. Speed of sound (SOS) is a QUS parameter (Haiat et al 2005b) that has been found to be related to bone strength (Haiat et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…As BMD and SOS are known to both decline with increasing age (1,16) and that BMD is altered by mass (17), partial correlations were conducted controlling for age, mass, and height (exploratory) separately and for all 3 combined. Linear regression was also conducted with each of the 3 SOS sites as a dependent variable with all BMD sites, age, mass, and height as predictor variables.…”
Section: Methodsmentioning
confidence: 99%
“…The Beam-Med Omnisense multisite quantitative ultrasound (mQUS) has been proven to prospectively predict fracture risk in women older than a 5-yr follow-up (1). The mQUS device assesses bone at distal radius (DR), tibia (TIB), and phalanx (PX) sites and provides an estimate of bone stiffness, expressed as speed of sound (SOS, in m/s).…”
Section: Introductionmentioning
confidence: 99%
“…QU is able to diagnose low BMD in GIOP and to predict future fractures [45], but its role in monitoring BMD changes and in predicting fracture risk in daily practice remains unclear.…”
Section: Other Techniquesmentioning
confidence: 99%